Sjögren's syndrome. - Brito, A (1994)
This paper consists the theorical review and the current concepts of the subject and the second includes the casuistry of the Stomatology Department of the Pulido Valente Hospital. From April 1989 to 1991 (2 years), a study was made on Sjögren Syndrome (Primary and Secondary) of multiple character with the particular co-operation of the Portuguese Institute of Rheumatology. With this paper we wish to point out the importance of the oral evaluation of the study of the plurisystemic diseases as well as to establish criterions of diagnosis for the Portuguese population. Eighty cases of suspected Sjögren's Syndrome have been assessed, 66 of which have been fully. The reason for the consultation was dry mouth, dry eyes and enlargement of parotid glands. The symptoms were isolated or in association with other pathologies after other causes had been excluded. We had to establish the salivary reference values for the Portuguese population in 22 healthy volunteers. The xerostomia was evaluated by the Sialochemistry, Sialography, Cintigraphy and biopsies of the lower lip and of the sublingual gland. The ophthalmologic examination took place in the Ophthalmology Department of Santo António dos Capuchos Hospital by means of Shirmer test, Rosa Bengala and B.U.T. In spite of Sjögren's Syndrome being, up to now, so remotely determined in connection with the treatment, these patients need medical care and Stomatology plays a fundamental role as far as the diagnosis and the therapeutic points of view are concerned. We maintain the notion that the Syndrome is not as infrequent as one would believe and the evaluation of the oral field is important to establish the degree of the disease and its treatment.